Shear strengths of joints with roughened concrete surfaces and post-installed dowel bars subjected to normal and shear stresses for seismically retrofitted structures. (November 2022) - Takase, Yuya; Yamada, Taizo
Abstract: When reinforced concrete (RC) structures are seismically retrofitted, new members are connected via joints with roughened surfaces and post-installed dowel bars. For retrofitted RC buildings, roughened surfaces are often manufactured using vibration hammers. However, investigations on the shear strengths of the joints subjected to shear and tensile normal stresses are limited. In this study, these joints, called hybrid joints, were subjected to shear loading. The test parameters were the normal stress, dowel bar diameter dd, and roughened concrete area ratio rrc . The normal stress was set to have a compressive stress σ0 of –0.48 N/mm 2 and a ratios rN of tensile stress to yield strength of 0.00, 0.33, and 0.66. In addition, dowel bars with dd  = 13, 16, and 19 mm were used. The target rrc values were 0.1, 0.2, and 0.3. Bearing failure of the roughened surface was observed as a result of the test. The shear strength decreased with increasing rN and decreasing rrc . Subsequently, an expression for the shear strength of a roughened surface was proposed. In this expression, the shape of an uneven surface was regarded as a cone. To estimate the shear strengths of the hybrid joints, the shear force from the previous dowel model was added to the proposed expression. Finally, the values obtained using the calculation method were compared with the test results. It was demonstrated that the proposed expression could reasonably estimate the test results, with a correlation coefficient of 0.93. In addition, for structural designs, the proposed expression should be multiplied times 0.7 to estimate the lower limit of the test results.